POTENSI BIOMASSA NIPAH (Nypa fruticans Wurmb.) DI DESA LUBUK MUDA KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Astuti, Jheni; Yoza, Defri; Sulaeman, Rudianda (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Biomass is organic material produced by photosynthetic process, either in the form of product or effluent. Plants, trees, grass, potatoes, agricultural waste, forest waste, excreta and cattle dung are examples of biomass. One of the potential biomass contained in mangrove ecosystem. Mangrove areas have important role for citizen especially in Riau Province on the mangrove palm region (Nypa fruticans Wurmb.). Riau Province is the largest region  in Indonesia covered by nypa plants. Nypa is a type of palm that grows in the area of the mangrove or sea tides. This research conducted in the Lubuk Muda Village Siak Kecil District Bengkalis and  Plant Ecophysiology Laboratory in the University of Riau in November 2014-January 2015. The aim of this study is to determine the potential of biomass nypa (Nypa fruticans Wurmb.) in Lubuk Muda Village Siak Kecil District Bengkalis. The result of this research showed biomass potential nypa in Lubuk Muda Village Siak Kecil District Bengkalis is 382,4 ton/ha or 19.120 ton when accumulated  to generality. Keywords: potential, biomass, nypa